Acute Toxicity Test of Jernang Resin Extract (Daemonorops Draco Willd.) on Male White Rats Sprague Dawley Strain - Lavlinesia; Mursyid; Fidia Yunita (Indonesian Food Science and Technology Journal, 2019)
Keywords— Jernang resin extract; white rats; acute toxicity